In Situ Synchrotron X-ray Diffraction of the Martensitic Transformation in Superelastic Ti-27Nb and NiTi Alloys: A Comparative Study. (2015) - Héraud, L.; Castany, P.; Lailllé, D.; Gloriant, T.
Abstract: In this study, the stress-induced martensitic transformations occurring in superelastic NiTi and Ni free titanium Ti-27Nb alloys were investigated by in situ synchrotron X-ray diffraction analyses during tensile tests. It was observed a direct β to α" martensitic transformation in the Ti-27Nb alloy while the intermediate R-phase was clearly observed to be stress-induced prior the B19'martensitic phase in the case of the NiTi.